Research progress in the prevention and treatment of liver fibrosis in Chinese medicine based on miRNAs molecular regulation of angiogenesis - Jiahui Wang; Xinhua Guo; Ruizhu Jiang; Jiaxi He; Tiejian Zhao; Yue Peng; Yang Zheng (Elsevier, 2022)
In recent years, liver fibrosis has become a hot research topic in the field of liver disease. Liver fibrosis is a healing response to trauma, it is not an independent disease, any liver injury is often accompanied by fibrosis, clinically there are many causes of liver fibrosis, such as viral hepatitis, alcoholic liver, fatty liver, autoimmune hepatitis and cholestatic hepatitis. The main pathological feature is the abnormal deposition of extracellular matrix (ECM), leading to the formation of fibrous scarring. Under physiological conditions, hepatic stellate cells (HSC) are in an inactive state and behave as quiescent cells, which are involved in the storage of vitamin A in the liver. When liver injury occurs, inflammatory mediators activate quiescent HSC to differentiate into myofibroblasts, which initiate tissue remodeling in the liver by secreting ECM proteins and matrix metalloproteinases. Transforming growth factor-β (TGF-β) is the most important fibrogenic factor identified, and platelet-derived growth factor (PDGF) is the most effective factor in stimulating HSC proliferation, differentiation and migration. PDGF receptors and ligands are upregulated in both experimental liver fibrosis models and human liver fibrosis disease. The development of liver fibrosis is a dynamic process, and the mechanism of its occurrence is very complex. Besides being related to astrocytes and cytokines, there are some other intricate factors, and the current studies cannot fully elucidate the mechanism. MicroRNA (miRNA)-mediated angiogenesis plays an important role in the development of liver fibrosis, and it has been shown that several miRNA molecules can modulate these targets to regulate angiogenesis and thus liver fibrosis. In addition, TCM can be used to treat liver fibrosis by modulating miRNA molecules and thereby regulating angiogenesis. Chinese medicine has the advantages of multi-target, good efficacy, low price and high safety, and it has a very broad prospect and in-depth exploration value in the study of the effect and mechanism of action of liver fibrosis treatment.